FACTORS AFFECTING STUDENTS’ READING ANXIETY IN EFL TEACHING AND LEARNING - Zamihu, Juamdan Zamha; Jusar, Nur Fitra (English Education Department, 2024)
The Problem statement of this research was what factors affecting the English reading anxiety for class XI.I students of SMA Negeri 4 Pasarwajo. The purpose of this study was to identify the factors that influence the reading anxiety of class XI.I students of SMA Negeri 4 Pasarwajo. This research used the qualitative research design. The subject of this research was student class XI.I SMA Negeri 4 Pasarwajo year 2022/2023. The data was obtained by observation and interview then was analyzed by the researcher with three steps: data reduction, data display, and draw conclusion or verification. This research found that there were three factors that affected the reading anxiety students’ class XI.I SMA Negeri 4 Pasarwajo. Those were hard to Understand Text, fear of making mistakes, lack of confidence.